2021
DOI: 10.3390/jcm10163499
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Septal Myectomy beyond 65 Years, with and without Concomitant Procedures

Abstract: Introduction and objectives: Septal myectomy remains the first septal reduction therapy for hypertrophic obstructive cardiomyopathy in young patients and those requiring concomitant procedures. Its role in advanced ages is questioned due to perceived increased risk. We assess the outcomes of surgical relief of obstruction in patients beyond 65 years old. Methods: A single-center retrospective review of patients ≥ 65 years old undergoing septal myectomy through median sternotomy between April 2015 and February … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
4
4
0
Order By: Relevance
“…Preoperatively, the majority of our subjects (59%) were either in NYHA class III or IV, with a mean IVS thickness of 24 ± 6 mm and a mean LVOT gradient of 93 ± 33 mmHg. In addition, postoperative outcomes at hospital discharge are in line with those observed in other surgical cohorts, with significant reduction in peak resting/provoked intraventricular gradient and significant improvement in heart failure symptoms [ 11 , 13 , 14 ]. A postoperative residual gradient of >30 mmHg was noticed in only 5 (6%) patients, consistent with literature data [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Preoperatively, the majority of our subjects (59%) were either in NYHA class III or IV, with a mean IVS thickness of 24 ± 6 mm and a mean LVOT gradient of 93 ± 33 mmHg. In addition, postoperative outcomes at hospital discharge are in line with those observed in other surgical cohorts, with significant reduction in peak resting/provoked intraventricular gradient and significant improvement in heart failure symptoms [ 11 , 13 , 14 ]. A postoperative residual gradient of >30 mmHg was noticed in only 5 (6%) patients, consistent with literature data [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 76%
“…In addition, postoperative outcomes at hospital discharge are in line with those observed in other surgical cohorts, with significant reduction in peak resting/provoked intraventricular gradient and significant improvement in heart failure symptoms [ 11 , 13 , 14 ]. A postoperative residual gradient of >30 mmHg was noticed in only 5 (6%) patients, consistent with literature data [ 14 , 15 ]. Notably, recent evidence from other groups, as well as our unpublished preliminary data, showed sustained improvement in hemodynamic and functional status during long-term follow-up [ 16 ].…”
Section: Discussionsupporting
confidence: 76%
“…Apart from similar mortality rates, older patients were more likely to undergo concomitant coronary artery bypass. Pruna-Guillen et al ( 16 ) showed that SM is an effective and safe procedure for elderly patients despite the need for concomitant procedures. In this series, the in-hospital mortality rate was 1.9% ( n = 1) and 84.6% of the enrolled patients underwent concomitant procedures, including aortic valve replacement, coronary surgery, and Maze procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the operation have been widely described previously by our mentors 25,26 with some additional left ventricular interventions if felt valuable to address certain HCM phenotypes as described in our experience by Pruna. 27 There are many other factors that play a role in the difficulty of the operation such as obesity, depth of patient chest, small aortic annuli, aortic root/valve rigidity, septal tissue consistency (presence of fibrosis or prior alcohol ablation) and also septal-to-floor angle.…”
Section: Insights Into the Operation And The Minimal Necessary Instru...mentioning
confidence: 99%